(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the significance of developmental centers established under Uzbekistan’s "Ilk Qadam" state educational program. These centers aim to enhance preschool children’s cognitive, social, physical, and creative skills through structured activities. The article discusses five key centers: Construction and Mathematics, Role-Playing and Theatrical Performance, Language and Speech, Natural Science and Environmental Studies, and Physical Development and Health. Each center fosters essential skills such as STEM learning, logical reasoning, social communication, language proficiency, and environmental awareness. The implementation of these centers supports children’s holistic development, preparing them for future academic success and social adaptation.